Degradation of Akt using protein‐catalyzed capture agents. (16th February 2016) - Henning, Ryan K.; Varghese, Joseph O.; Das, Samir; Nag, Arundhati; Tang, Grace; Tang, Kevin; Sutherland, Alexander M.; Heath, James R.
Abstract : Summary: Abnormal signaling of the protein kinase Akt has been shown to contribute to human diseases such as diabetes and cancer, but Akt has proven to be a challenging target for drugging. Using iterative in situ click chemistry, we recently developed multiple protein‐catalyzed capture (PCC) agents that allosterically modulate Akt enzymatic activity in a protein‐based assay. Here, we utilize similar PCCs to exploit endogenous protein degradation pathways. We use the modularity of the anti‐Akt PCCs to prepare proteolysis targeting chimeric molecules that are shown to promote the rapid degradation of Akt in live cancer cells. These novel proteolysis targeting chimeric molecules demonstrate that the epitope targeting selectivity of PCCs can be coupled with non‐traditional drugging moieties to inhibit challenging targets. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Highlights: An Akt‐targeted PCC allosterically activates Akt kinase activity in cells The anti‐Akt PCC was functionalized with a degradation tag to create a novel PROTAC Combining PCCs with degradation tags is a new strategy to create PROTACs In Brief: A protein‐catalyzed capture agent (PCC) was developed against the C‐terminal hydrophobic motif of Akt, a traditionally 'undruggable' site, and shown to be an allosteric activator. Functionalization of the PCC with a degradation tag led to a new anti‐Akt PROTAC. Abstract : A protein‐catalyzed capture agent against the serine/threonine kinase Akt was functionalized for live‐cell imaging and in‐cell activation and degradation of Akt. Protein‐catalyzed capture targeting and modularity are useful for non‐traditional protein‐targeting strategies